KEMAMPUAN MANAJERIAL KYAI DALAM MENGELOLA PONDOK PESANTREN AL-ITTIFAQ - Sri Widaningsih (STKIP Pesisir Selatan, 2023)
The important meaning of management implementation of the boarding school is very helpful for the achievement of educational goals. This study aims to portray and analyze the managerial skills of a Kyai in process to manage a boarding school. This study uses qualitative methods with a